إسهام العلماء في الحياة الاجتماعية والثقافية بالجزائر في أواخر العهد العثماني - الزين, محمد (جامعة الوادي - University of Eloued, 2019)
Some writings by European travelers who visited Algeria during the Ottoman reign revealed that cultural life was lively and that the scientific and literary activity was spread throughout the territory. The notoriety of most Ulema, men of Islamic jurisprudence (foukahaa), men of letters and thinkers went beyond the borders to settle in the Arab and Islamic countries. We will try through our modest article to look at the contribution of ulemas and the role played in social and cultural life in Algeria at the end of the Ottoman era while highlighting their impact on society and the social status occupied.
مقال
Keywords: الرحالة الأوروبيون,الفترة العثمانية,الحياة الإجتماعية والثقافية; European travelers - Algeria - Ottoman reign - social and cultural life - oulémas